ISLAMIZATION OF EDUCATION IN MALAYSIA: THE INFLUENCE AND LEGACY OF ISMAIL RAJI AL-FARUQI - Salam, Abdul Hanan bin Abdul; Hussin, Nur Syamim Syahirah Mat (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
Ismail Raji al-Faruqi’s vision of the Islamization of Knowledge (IoK) has profoundly influenced Malaysia’s education system, shaping both policies and pedagogical approaches. His engagement with Malaysian scholars and political figures, including Syed Naquib al-Attas, Anwar Ibrahim, and Mahathir Mohamad, contributed to integrating Islamic principles into national education. This influence is reflected in the Malaysian National Education Philosophy, which emphasizes holistic development grounded in Islamic values. At the school level, the integration of Islamic studies into general education has been expanded through policies that blend religious and secular knowledge. The establishment of Islamic secondary schools and tahfiz institutions underscores the government’s efforts to develop an education system aligned with Islamic teachings. Additionally, tertiary institutions have introduced Islamic perspectives in various disciplines, including science, law, and economics, aiming to produce professionals guided by ethical and religious principles. Beyond traditional education, al-Faruqi’s influence extends to professional fields such as public health, where Islamic values have been incorporated into medical ethics and healthcare training. However, the implementation of IoK faces challenges, particularly criticisms that non-Western frameworks may not align with global academic standards or local funding priorities. Furthermore, the increasing influence of Western educational models, market-driven policies, and accreditation demands has led to debates over whether the Islamization agenda is being diluted. This paper explores the extent to which al-Faruqi’s IoK principles continue to shape Malaysia’s education system amidst these evolving challenges. It argues that while efforts to integrate Islamic values persist, there is a need for continuous dialogue to balance Islamic epistemology with modern educational demands, ensuring that knowledge remains both relevant and rooted in ethical and spiritual foundations.